If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 + -9x + -7 + -6x = 7 Reorder the terms: 11 + -7 + -9x + -6x = 7 Combine like terms: 11 + -7 = 4 4 + -9x + -6x = 7 Combine like terms: -9x + -6x = -15x 4 + -15x = 7 Solving 4 + -15x = 7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -15x = 7 + -4 Combine like terms: 4 + -4 = 0 0 + -15x = 7 + -4 -15x = 7 + -4 Combine like terms: 7 + -4 = 3 -15x = 3 Divide each side by '-15'. x = -0.2 Simplifying x = -0.2
| (x-2)+2(x-2)-24=0 | | -2p-6p=-24 | | 7=8x-4 | | (4x^2+16x+16)(x-2)=x^2-4 | | 2x^4-7x^2+2=0 | | 2t-3=3(t-4) | | 2-0.6k=2 | | 36=3(4-x) | | 5x+x=8x+55+9x | | 25x-3=35x+5 | | 2p^3*6p^4= | | 20*.15= | | 8y-7-6y+2=0 | | 3x+27=20x-43 | | x/9+4=13 | | -9(x-4)+5x=-4(x+8)+5 | | 9*19+9= | | 2(4x+9)=-42+36 | | -x^2+8x-52=0 | | 12=4r-8+6r | | 4x-1(60-x)=130 | | 12/3x2/8 | | 1/2y-8=-7 | | 2+x=94 | | 7(y+9)+y=2(y+5)+4 | | 3x^2-12x-38=0 | | (12+8x)+13= | | 2x+5=7-2x | | 4th=60+10t | | 9x-5+3x+2= | | 3x^3-7x+6x-14=0 | | 0.3x=0.51 |